Prevalence of urinary incontinence and its determinants among pregnant women in Addis Ababa, Ethiopia - Weldetensaye, Eskinder Kebede (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To establish the prevalence of urinary incontinence and its determinants among pregnant women in Addis Ababa, Ethiopia. Methods: This was a facility based cross-sectional study. Data was collected in July 2016 by trained data collectors using the International Consultation on Incontinence criteria qualified questionnaire interviewing333 consenting pregnant women aged 15 to 42 years who were attending antenatal care (ANC) through an exit interview. Data was entered and cleaned using Epi Info, and analyzed using SPSS version 20.0 statistical software. The univariate analysis such as proportions, percentages, ratios, frequency distributions and appropriate graphic presentations were used for describing data. Bivariate analysis of socio-demographic, co-morbidities, mode of deliveries, and parity were included. Then multivariate logistic regression model was employed to control confounding factors. Results: A big number of the pregnant women, 82(24.6%), reported Urinary Incontinence. Thirty-eight (11.4%) reported stress urinary incontinence (SUI) only and 15 (4.5%) reported urge incontinence (UUI) only while 29 (8.7%) reported mixed stress and urge incontinence during the preceding month. Seven women (8%) had moderate or severe symptoms. Out of the 82 cases, only 18 (21.9%) had consulted a health-care professional. A total of 9 (23.7%) of women with SUI, 3 (20%) of those with UUI and 6 (20.7%) with MUI had sought help for urinary symptoms. Treatment seeking was related to severity (measured as frequency of leakage), with 17% of treatment seekers leaking monthly or less often, 39% leaking weekly and 44% leaking daily, whereas 25% of non-treatment seekers leaked monthly or less, 53.1% leaked weekly and 21.9% leaked daily. The commonest reason not to seek help was that it was considered as normal and common during pregnancy. The determining factor for prevalence of UI was the mode of delivery. Those pregnant women who delivered by C/S had only lower odds to be urinary incontinent (AOR: 0.46:95%CI (0.22, 0.98) than those women who delivered vaginally. Storage phase symptoms (nocturia, urgency and daytime frequency) were common among respondents. Of these, nocturia was the commonest with 85% of reporting respondents. Conclusions: This study showed that many pregnant women in Ethiopia suffer in silence from a variety of lower urinary tract symptoms, at levels comparable to their counterparts in other parts of the world. There is a need to create awareness among health care providers on the lower urinary tract related morbidities in pregnancy and build their capacity to recognize, investigate and manage these symptoms.